2017
DOI: 10.1055/s-0037-1608660
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Quercetin on Necrotizing Enterocolitis in a Neonatal Rat Model

Abstract: QE is effective in enhancing antioxidant defense mechanism, limiting oxidative stress, reducing intestinal damage, and preventing NEC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Numerous studies have shown that quercetin has the potential to treat other diseases, such as necrotizing enterocolitis (NEC), diabetes, and lung injury. In NEC, quercetin modulates the total antioxidant status by regulating serum levels of MDA and GSH [101]. In type II diabetes, a study found that quercetin intake was inversely related to the prevalence of diabetes [102].…”
Section: Application Of Antioxidant Activity In the Medicinal Fieldmentioning
confidence: 99%
“…Numerous studies have shown that quercetin has the potential to treat other diseases, such as necrotizing enterocolitis (NEC), diabetes, and lung injury. In NEC, quercetin modulates the total antioxidant status by regulating serum levels of MDA and GSH [101]. In type II diabetes, a study found that quercetin intake was inversely related to the prevalence of diabetes [102].…”
Section: Application Of Antioxidant Activity In the Medicinal Fieldmentioning
confidence: 99%
“…Other disease conditions like necrotising enterocolitis (NEC), respiratory infections may be treated with quercetin. By lowering the level of oxidative stress biomarkers and enhancing antioxidant enzyme activity, it protects against acute lung injury [23]. respiratory illnesses.…”
Section: Therapeutic Applications Of Quercetinmentioning
confidence: 99%
“…Here, we summarize the recent studies that have evaluated the biological and pharmacological activities of quercetin (Table 1 (Tab. 1) ; References in Table 1: Abdelhalim et al, 2018[ 1 ]; Afifi et al, 2018[ 2 ]; Aghapour et al, 2018[ 3 ]; Ahmed et al, 2018[ 4 ]; Al-Asmari et al, 2018[ 5 ]; Ansar et al, 2016[ 7 ]; Atef et al, 2017[ 8 ]; Beghoul et al, 2017[ 9 ]; Calgarotto et al, 2018[ 11 ]; Chan et al, 2018[ 12 ]; Chang et al, 2017[ 13 ]; Chen et al, 2017[ 14 ]; Damiano et al, 2018[ 16 ]; Dong et al, 2017[ 17 ]; Duranti et al, 2018[ 18 ]; Esrefoglu et al, 2017[ 20 ]; Funakoshi et al, 2017[ 22 ]; Guo et al, 2017[ 23 ]; He et al, 2016[ 24 ]; Huang et al, 2017[ 25 ]; Jeon et al, 2017[ 26 ]; Ji et al, 2017[ 27 ]; Ju et al, 2018[ 28 ]; Kee et al, 2016[ 29 ]; Lan et al, 2017[ 30 ]; Lazo-Gomez and Tapia, 2017[ 31 ]; Li et al, 2018[ 32 ]; Liu and Zhou, 2017[ 34 ]; Liu et al, 2017[ 35 ]; Lu et al, 2018[ 36 ]; Maciel et al, 2016[ 37 ]; Maksymchuk et al, 2017[ 38 ]; Mitani et al, 2017[ 40 ]; Mkhize et al, 2017[ 41 ]; Naseer et al, 2017[ 42 ]; Pandya et al, 2017[ 45 ]; Patrizio et al, 2018[ 46 ]; Qin et al, 2017[ 47 ]; Ren et al, 2018[ 48 ]; Sameni et al, 2018[ 49 ]; Singh et al, 2018[ 51 ]; Sohn et al, 2018[ 52 ]; Tinay et al, 2017[ 53 ]; Veith et al, 2017[ 54 ]; Wu et al, 2018[ 55 ]; Xingyu et al, 2016[ 56 ]; Yang et al, 2017[ 57 ]; Yang et al, 2018[ 58 ]; Yarahmadi et al, 2017[ 60 ]; Yarahmadi et al, 2018[ 59 ]; Yazıcı et al, 2018[ 61 ]; Yuan et al, 2016[ 63 ]; Yuan et al, 2018[ 62 ]; Zhang et...…”
mentioning
confidence: 99%